IONIC LIQUID PRETREATMENT COMBINED WITH ENZYMATIC DELIGNIFICATION FOR SEPARATION OF CELLULOSE RICH FIBERS FROM OIL PALM BIOMASS - ,, REVIE FINANCIE (2015)
Oil Palm biomass (OPB) - the most abundant lignocellulosic resources in the Malaysia- represents an abundant carbon-neutral renewable resource for bioenergy and biomaterials production. OPB is mainly composed of three subcomponents called cellulose, hemicellulose and lignin. Among these biopolymers, celluloses have been used as source of raw materials for biocompatible and biodegradable materials production due to their fascinating structure and excellent properties. However, structural complexity and heterogeneity ofcell-wall microfibrils in OPB is the biggest challenge for the clean separation of celluloses with minimal structural alteration. A number of pretreatment methods including physical, physico-chemical, chemical and enzymatic delignification methods have been used for separation of celluloses from OPB. Among these, enzymatic delignification for degrading lignin has received much attention as an environmentally safe process.